2017
DOI: 10.1111/and.12819
|View full text |Cite
|
Sign up to set email alerts
|

Can haematologic parameters be used for differential diagnosis of testicular torsion and epididymitis?

Abstract: A differential diagnosis of testicular torsion and epididymitis has serious importance for testicular health. In emergency conditions, if testicular torsion goes unnoticed and epididymo-orchitis is diagnosed, organ loss may occur. This study aimed to evaluate the usefulness of haematologic parameters for the diagnosis of both testicular torsion and epididymo-orchitis and for differential diagnosis of these two diseases. Patients were divided into three groups as those undergoing surgery for testicular torsion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 27 publications
3
36
3
Order By: Relevance
“…According to the inclusive and exclusive criteria, six were excluded for various reasons after reading the full texts. Ultimately, a total of five case–control studies remained in the final analyses (Bitkin et al, ; Cicek et al, ; Güneş et al, ; Peretti et al, ; Yucel & Ozlem Ilbey, ). The flow chart of literature retrieval and selection process was outlined in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the inclusive and exclusive criteria, six were excluded for various reasons after reading the full texts. Ultimately, a total of five case–control studies remained in the final analyses (Bitkin et al, ; Cicek et al, ; Güneş et al, ; Peretti et al, ; Yucel & Ozlem Ilbey, ). The flow chart of literature retrieval and selection process was outlined in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some investigators reported that haematologic parameters at admission (including mean platelet volume [MPV], platelet lymphocyte ratio [PLR], neutrophil–lymphocyte ratio [NLR], platelet [PLT] and leucocyte) are different between TT and epididymo‐orchitis patients. Therefore, these haematologic parameters may have potential as diagnostic markers for TT (Bitkin et al, ; Cicek, Togan, Akbaba, Narci, & Aygun, ; Güneş et al, ; Peretti et al, ; Yucel & Ozlem Ilbey, ). Of these studies, controversy and inconformity still remained and most of them recruited a limited sample capacity, which is insufficient to get a firm conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Bitkin et al . reported that leukocyte, MPV, and NLR might be used in the diagnosis of epididymitis and testicular torsion and platelet counts and PLR might be useful to differentiate epididymitis from testicular torsion (Bitkin et al ., ). Ventimiglia et al .…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Güneş et al, () reported that MPV did not have diagnostic ability for TT, but NLR did, by comparing 75 TT patients with 56 age‐matched healthy subjects. Bitkin et al, () found that MPV was increased in children with testicular torsion and epididymitis, but it was not different between the two groups. Nevertheless, they suggested that routine blood tests provide a rapid and inexpensive platform of diagnosing TT.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have reported that haematologic parameters can be used for the differential diagnosis of TT (Bitkin et al, ; Cicek, Togan, Akbaba, Narci, & Aygun, ). But to our knowledge, only one study by Jang et al have reported the association between haematologic parameters and the testicular salvage rate.…”
Section: Discussionmentioning
confidence: 99%